1968
DOI: 10.1042/bj1080161
|View full text |Cite
|
Sign up to set email alerts
|

Further purification and characterization of the acid α-glucosidase

Abstract: 1. Centrifugation of rat liver acid glucosidase, which had been purified by adsorption on dextran gel, on a density gradient of sucrose showed the enzyme to be impure. 2. Preliminary purification of the enzyme before the gel filtration improved the final degree of purity of this preparation. Disc gel electrophoresis of this preparation showed a single band of protein. 3. The sedimentation co-efficient and the molecular weight determined on a sucrose gradient were 4.9-5.1s and 76000-83000 respectively for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1969
1969
1983
1983

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 11 publications
(8 reference statements)
1
18
0
1
Order By: Relevance
“…Using data from figure 5, /C m -values for acid α-glucosidase were determined by Michaelis-Menten, Lineweaver-Burk and Hanes plots; the mean value was 11.5 mmol/1 for the unstimulated enzyme and 2.8 mmol/1 for the potassium ion-stimulated enzyme. Similar # m -values were found for the unstimulated acid α-glucosidase from human urine (2) and human kidney (12). Potassium ions caused an increased affinity of acid α-glucosidase for maitose, s well s an increased rate of maitose hydrolysis ( fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Using data from figure 5, /C m -values for acid α-glucosidase were determined by Michaelis-Menten, Lineweaver-Burk and Hanes plots; the mean value was 11.5 mmol/1 for the unstimulated enzyme and 2.8 mmol/1 for the potassium ion-stimulated enzyme. Similar # m -values were found for the unstimulated acid α-glucosidase from human urine (2) and human kidney (12). Potassium ions caused an increased affinity of acid α-glucosidase for maitose, s well s an increased rate of maitose hydrolysis ( fig.…”
Section: Resultssupporting
confidence: 80%
“…Glucose concentrations up to 5 mmol/1 in the samples did not disturb the determination of acid α-glucosidase. The activity of acid α-glucosidase is inhibited by tris and by erythritol (12).…”
Section: Selectivity Of the Assay For Neutral α-Glucosidasementioning
confidence: 99%
“…Because purified AM preparations from rat liver (Jeffrey, Brown, and Brown, 1967;Auricchio, Bruni, and Sica, 1968) and from human kidney (Auricchio et al, 1968) were found recently to have Km values of 5 x 10-3M and 13-6 x 10-3M, respectively, with maltose as substrate, it seemed possible that the enzyme in muscle homogenates was suboptimally active at the 5 mM substrate concentration originally recommended by Hers (1963). Maltose hydrolysis was therefore determined with increasing concentrations of maltose in three cases of AM deficiency in adults, in six heterozygotes and in two non-weak and two neuromuscular disease controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…She demonstrated progressive muscle weakness and muscle wasting since the age of 30 yr. She died at the age of 47 yr because of respiratory failure. Skin fibroblasts were cultured and harvested at early confluence as described (17 (19). A 4.5 x 45-cm column was used to increase the flow rate.…”
Section: Skin Fibroblastsmentioning
confidence: 99%